The effect of extrinsic and intrinsic rewards on employee performance with mediator of distributive justice at full-fledged Islamic banks in Malaysia - Mohammed, Uji @ Rozita; Jetrine, Nur Adibah (Universiti Teknologi MARA, Terengganu, 2025)
The issues of unfairness rewards that can affect the employee’s performance makes this study aims to examine the effect and relationship between intrinsic and extrinsic on employee performance with mediator of distributive justice at full-fledged Islamic banks in Malaysia. Besides, the equity theory is used since it has relations in explaining the rewards and employee performance with mediation of distributive justice as well as in the methodology, a questionnaire (5-Likert Scale) is designed to collect relevant data and the minimum required sample size in this study needs about 77 respondents. The data will be analysed using Statistical Package for the Social Sciences (SPSS) and Partial Least Square-Structural Equation Modelling (PLS-SEM) analysis. The population that will be chosen is the employees from executive, non-executive and managerial positions who work with Islamic Banks in Malaysia (Sabah states). The findings revealed that both rewards (extrinsic and intrinsic) and employee performance has a significant effect and relationship to distributive justice as a mediator variable. To ensure equitable and equal distribution of rewards among employees, organizations should establish their policies, organizational structures, and reward systems. This will undoubtedly improve the organization's growth and goodwill. The organizations should design their policies, organizational structures and reward systems that ensure just and fair based distribution of rewards among employees and it surely led to enhance the goodwill and growth of organization.